The effectiveness of whatsapp in vocabulary learning - Kasturi, Sivabalan; Zuraina, Ali (Universiti Teknologi Malaysia, 2022)
Vocabulary is the backbone and prominent feature in language acquisition. Limited vocabulary causes a major breakdown in both written and oral communication which inflicts inefficiency among Malaysian students despite being exposed to the vocabulary for more or less than 11 years.